Post colonoscopy ischemic colitis: a case and literature review - Sadeghi, Amir; Kishani Farahani, Zeinab; Pashai, Mohammad Reza; Kazemi, Shamim; Jamshidfar, Negin (Researcher Bulletin of Medical Sciences, 2018)
Ischemic colitis is the most common form of intestinal ischemia and is more common in the elderly and among individuals with risk factors for ischemia. Ischemic colitis is a rare complication of colonoscopy. The predisposing conditions for developing ischemic colitis following colonoscopy are connective tissue disease, advanced age and cardiovascular disease. Ischemic colitis may rarely occur following a colonoscopy without these risk factors. The data collection of 22 case of ischemic colitis (21 cases in previous reports and one case in our case) were reviewed. Here, we report a case of ischemic colitis after a routine colonoscopy in patient without risk factors for ischemia. Conclusion: Colonoscopy could be induced ischemic colitis, that should be brought to attention of gastroenterologist.